Gender Role on MSME Performance Through Entrepreneurial Behaviour and Ease of Access to Capital - Sudarnice sudarnice; Andry Stepahnie Titing; Supiani Supiani; Titin Juniarti (University of Merdeka Malang, 2024)
In order for MSMEs to remain competitive in an unstable market circle, the digital era, especially after the current COVID-19 pandemic crisis, the performance of MSME needs to be improved. However, the performance of MSME in Indonesia is unfortunately still overshadowed by the issue of gender equality which is related, among others, to ease access to capital in running their business. Therefore, the purpose of this study was to examine the direct and indirect relationship between gender and MSME performance through entrepreneurial behaviour and ease of access to capital. The steps applied to this research started with collecting data, the researcher took a list of MSMEs in Muna Regency with a total sample of 106 MSME. Data can be obtained by interviewing and administering questionnaires to MSME managers or owners, then factor analysis is carried out using the Structural Equation Modeling (SEM) concept with the Partial Least Square (PLS) program. The results of our analysis show that there is no direct influence between gender on MSME performance but there is an indirect effect through entrepreneurial behaviour and easy access to capital.